1991
DOI: 10.2331/suisan.57.1501
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in the Anal Fin of Ayu Plecoglossus altivelis.

Abstract: Sexual dimorphism in the anal fin of ayu Plecoglossus altivelis was studied by serial sampling of ayu. Changes in the shape of the anal fin were triggered by sexual maturation in both sexes; however, secondary sexual characteristics developed drastically in males while they did so inconspicuously in females.The anal fin base became larger in both sexes during sexual maturation, but grew much faster in males than in females, and consequently males have larger anal fin bases than females. Secondary changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The sexual size dimorphism revealed here is consistent with other findings that male fish are generally bigger than females (Iguchi et al, 1991;Oliveria and Almada, 1995;Park et al, 2001). In Lake Tanganyika cichlids, the most extreme sexual dimorphism was observed in the shell-brooding Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The sexual size dimorphism revealed here is consistent with other findings that male fish are generally bigger than females (Iguchi et al, 1991;Oliveria and Almada, 1995;Park et al, 2001). In Lake Tanganyika cichlids, the most extreme sexual dimorphism was observed in the shell-brooding Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In male cocktail wrasse, changes in the first and second spiny rays of the dorsal fin are more pronounced in the breeding season and are not present in sexually immature fish. Sexual dimorphic characterics in fish structure have been noted in other fishes (Iguchi et al, 1991;Oliveria & Almada, 1995). Lee et al (1992) found body colour changes in protogynous bagridae.…”
mentioning
confidence: 96%
“…Furthermore, it may be worthwhile to note that estrogenic control in the forebrain and midbrain of males is relatively similar to that of females because androgenic control of the forebrains and midbrains is abundant. In many teleost fish, it is known that levels of sex hormone receptors between males and females are different in the gonads, liver, brains and blood serum depending on the season (Owen 1936, Iguchi et al 1991, Du et al 2004, Desjardins et al 2006). In the breeding season, the levels of androgens were high in male oyster toadfish, Opsanus tau, and showed obvious sexual dimorphism (Fine et al 2004).…”
Section: Discussionmentioning
confidence: 99%